Benefits of intervention for Post-Traumatic Stress Disorder in soldiers. A systematic review (Revista Estudios Psicológicos, 2022)
Background: Nowadays, the Army, consisting of Land, Air, and Sea, demands a constant work in the service of the nation, being the first duty of the military the permanent disposition of the national defense. Consequently, its members have to face several stressful situations during their professional career. Aim: To identify, through a systematic review, the influence of intervention programs on Post-Traumatic Stress Disorder (PTSD) in professional military personnel. Materials and methods: Systematic review in five multidisciplinary databases using two search formulas in English and Spanish, following Cochrane recommendations and the phases of the PRISMA guide. The selection of studies was made by two readings, guaranteeing completeness and reproducibility. Results: Two studies were included with a total of N = 263 participants. The results show a relationship between participation in Zone of Operations (ZO) and PTSD in professional military personnel. Conclusion: PTSD negatively affects the physical and psychological health of the soldier. Consequently, it is relevant to intervene through programs to reduce PTSD. Finally, the importance of EI, resilience and support, both family and social, to alleviate the effects of PTSD is highlighted.
Keywords: welfare; professional military; systematic review; soldiers; PTSD